Characteristics of Dissolved Organic Matter and Trihalomethane Forming Potential Occurrence in Watersheds with Different Upstream Land Use: 10.32526/ennrj/21/202200179 - Dirgawati , Mila; Sururi, Mohamad Rangga (Environment and Natural Resources Journal, 2023)
Dissolved organic matter (DOM) is the most important natural organic matter (NOM) fraction which reacts with chlorine to form harmful trihalomethanes (THMs) in water bodies. The characteristics of DOM could be affected by land use in the catchment, hence comprehensive study to understand DOM in the water body is important. This study was conducted in two watersheds with different upper stream land use to determine: (1) water characteristics, total organic matter (TOM), and DOM quality and quantity based on optical and absorption properties; (2) fluorescence dissolved organic matter (FDOM) compounds; (3) TOM and DOM relationships; and (4) THMs forming potential (THMFP) in both watersheds. Samples were collected from the upper Cimahi and Cijanggel Rivers which are dominated by settlements and plantations, respectively. Water characteristics were determined by pH, electroconductivity (EC), nitrite, and nitrate in unfiltered and filtered samples. TOM and DOM were characterized by chemical oxygen demand (COD) and chromophoric DOM (CDOM) parameters (A254, A355, A3/4), and organic compounds were determined as FDOM compounds. The measured pH, nitrate, and nitrite in the settlements-impacted watershed were greater than those in the plantations-impacted watershed. The main FDOM compounds in the settlement-impacted river were tryptophan microbial byproduct (T1) and tryptophan aromatic protein (T2), fulvic acid (A), and humic acid (C). Meanwhile, in the plantations-impacted river were T1, A, and C. THMFP was detected in both rivers which were greater in the plantations-impacted watershed than the settlements-impacted watershed.